Capnocytophaga sputigena bloodstream infection in hematopoietic stem cell transplantations: two cases report and review of the literature - Fernanda Rodrigues Mendes; Felipe Ribeiro Bruniera; Jayir Schmidt; Ana Paula Cury; Camila Rizeck; Hermes Higashino; Fernando Nivaldo Oliveira; Flavia Rossi; Vanderson Rocha; Silvia Figueiredo Costa (Revista do Instituto de Medicina Tropical de São Paulo, 2020)
ABSTRACT Capnocytophaga is a group of facultative anaerobic gram-negative bacteria present in the oral cavity of humans, dogs and cats, as part of their normal oral flora. Here, we described two cases of bloodstream infections (BSI) caused by Capnocytophaga in neutropenic autologous hematopoietic stem cell transplantation (auto-HSCT) patients with mucositis (Grade I and Grade III) identified by Maldi-Tof. They were successfully treated with β-lactam (meropenem and piperacillin-tazobactam). The species C. sputigena was confirmed by 16S rRNA gene sequencing in one patient. The review of literature showed that C. ochraceae was the most frequent species causing BSI in auto-HSCT patients and that the patients usually presented mucositis and were neutropenic at the onset of the infection.